PENDAMPINGAN BELAJAR AL QURAN SISWA DENGAN METODE IQRO DI TPA JANNATUL FIRDAUS SIMAN PONOROGO - Yusuf Al Manaanu; Saipul Nasution; Achmad Arif; Salman Al Farizi; Muhammad Azrul Amirullah; Rizky Cahya Aulia Bahtiar; Muhammad Habibi Albana (LPPI UMN AL WASHLIYAH, 2025)
Learning assistance for students at Taman Pendidikan Al-Qur'an (TPA) Jannatul Firdaus using the Iqro method is an effort to develop students' ability to read the Qur'an and deepen their understanding of Islamic teachings. This community service aims to evaluate the effectiveness of the Iqro method in improving Qur'anic reading skills, comprehension of Islamic values, learning motivation, as well as students' listening and speaking skills. This activity employs a qualitative approach with a case study method. Data collection was conducted through direct observation, interviews with educators, and document analysis. During the learning assistance period, students received intensive instruction using the Iqro method, which included the introduction of hijaiyah letters, step-by-step Iqro lessons, and interactive activities to strengthen students’ understanding. The results of the program indicate that the learning assistance using the Iqro method had a positive impact on improving students’ ability to read the Qur'an, understand Islamic teachings, increase their motivation to learn, and enhance their communication skills. Through a structured approach and well-organized learning schedules, students at TPA Jannatul Firdaus were able to make significant progress in their Qur'anic studies